Insights into Tripodal Tris(pyrazolyl) Compounds as Ionophores for Potentiometric Ammonium Ion Sensing. Issue 18 (23rd September 2022) - Colozza, Noemi; Casanova, Ana; Fernández‐Pérez, Bibiana M.; Crespo, Gaston A.; Flores, Gabriel A.; Kavallieratos, Konstantinos; de Gracia, Juan; Ahlquist, Mårten; Cuartero, Maria
Abstract: The decentralisation of accurate determination of the ammonium ion (NH4 + ) is relevant for environmental monitoring (i. e., nitrogen cycle) and certain clinical applications (e. g., kidney and liver diseases). Potentiometric ionophore‐based sensors are one alternative for these purposes in terms of versatile implementation, though the potassium ion (K + ) is known to be a major source of interference. We herein investigate the use of three different tripodal tris(pyrazolyl) compounds derived from 1, 3, 5‐triethylbenzene as NH4 + ionophores. A complete set of potentiometric experiments together with theoretical simulations reveals suitable analytical performance while demonstrating a suppression of the K + interference given the formation of an adequate cavity in the ionophore to host NH4 + over K + in the membrane environment. The results support the use of these electrodes in the analytical detection of NH4 + in a wide range of samples with variable contents. Abstract : Potentiometric sensing : The use of tripodal tris(pyrazolyl) compounds derived from 1, 3, 5‐triethylbenzene as the ionophore element in potentiometric sensors allows for enhanced response of NH4 + over K + . This facilitates the accurate determination of NH4 + in a wide range of samples.